Explicating failure among nascent entrepreneurs in West Sumatra: The nexus of psycho-economic factors and opportunistic behavior - Hafiz Rahman; Eri Besra; Nurhayati (Journal of Entrepreneurship, Management and Innovation)
This paper investigates and discusses individuals’ internal circumstances as factors that may cause entrepreneurial failure, which consists of psycho-economic phenomenon and opportunistic behavior of individuals. The study is a quantitative study, and it operates relational analysis that relates existing arguments regarding psycho-economic factors to entrepreneurial failure. The study further adds and analyses the construct of opportunistic behavior as another possible factor that may cause entrepreneurial failure. The sample of the study is 1541 young entrepreneurs in West Sumatra Province, Indonesia, who have experienced failures in their previous businesses. The analysis was undertaken by using multiple and partial regression analysis in which the statistical protocol was operated. It is found that psycho-economic factors, together with opportunistic behavior of individuals in a lesser to a greater degree, have caused entrepreneurial failure to the context of the study. The study also implies and argues that opportunistic behavior may not only be viewed as a source of entrepreneurial success, as it also contributes to entrepreneurial failure. This finding clearly demonstrates the originality and value of this study since it argues that opportunistic behavior can also be viewed as a factor – apart from the other existing psycho-economic factors (deterministic, voluntaristic, and emotive) – that can cause entrepreneurial failure. The study further suggests that strengthening entrepreneurial personality, characteristics and psychological aspects should be a focus for the Indonesian government in promoting and developing young-nascent entrepreneurs.